The social responsibility in healthy municipalities for the peace strategy. case study (2000)
During 1987 and having as main motivation the need to solve a series of social problems suffered by the population, the municipality of Versalles in the Valle of the Cauca began to develop a work very close to the strategy of "Healthy municipalities for the peace", even through it was not properly framed within that strategy at that movement. In 1992 Pan American Health Organization began a technical cooperation program with the municipality, which was aimed to favor the work towards the consolidation of the town as a "Healthy town". A process that in 1995 resulted in the fact that the town of Versalles became classified as a Healthy Municipality by the Peace"; from then on Versalles has been recognized like a model municipality, and its experience has been presented at international level as one of the most successful of the strategy. The process in Versalles has like a key of success the importance that was given to its community and the educational work looking for the development of social abilities both at individual and cultural level. The basic aim of the strategy of Healthy Municipalities for the peace in this town has been the generation of richness in the society, both in social and cultural terms, a process in which the social and ethical values were at the center of all the actions that have been doing.